B4C-containing composite ceramic and preparation method thereof
By adopting pressure change cycle sintering technology during the sintering of ceramic materials, the problems of uneven distribution of ceramic materials and the second phase are solved, and the preparation of composite ceramic materials with high density, high hardness and uniform mechanical properties are achieved, which simplifies the Preparation process.
Patent Information
- Application Number
- CN202411286683.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-03
AI Technical Summary
During the sintering process, the density of existing ceramic materials is difficult to improve due to insufficient constant pressure, and the second phase is unevenly distributed, which affects the mechanical properties.
The pressure change cycle sintering technology is adopted, and the constant pressure is adjusted to dynamic pressure by pressurizing and decompression treatment at a specific temperature, which destroys the agglomeration of ceramic powders, improves the sintering driving force, and achieves uniformity of the second phase distribution.
It significantly improves the density, hardness and fracture toughness of composite ceramics, and has uniform distribution of mechanical properties, simplifies the preparation process, and has good practical application value.
Smart Images

Figure CN119241247A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite ceramics, and in particular relates to a composite ceramic containing B4C and a preparation method thereof. Background Art
[0002] Structural ceramic materials are known for their excellent mechanical properties such as high melting point, high hardness, high rigidity, low density, corrosion resistance and impact resistance. Therefore, they have broad application space in the fields of energy, metallurgy, aerospace, modern communications, bulletproof armor, etc., and have become an indispensable key material in the modern industrial system. Among the many structural ceramic materials, boron carbide (B4C) is undoubtedly one of the materials with the most application potential. In B4C, the covalent bond ratio of boron to carbon is as high as over 93%. The special bonding characteristics make it have extremely high hardness (Vickers hardness>30GPa), and its hardness value is only lower than diamond and cubic boron nitride. It also has a high melting point (2427℃), low density (2.52g·cm -3 ), high elastic modulus (450~470GPa), as well as excellent chemical stability, cross-sectional neutron absorption, impact resistance and wear resistance. However, the extremely high covalent bond ratio also means that only when the temperature is above 2000℃ will the boron carbide grains undergo grain boundary and volume diffusion to accelerate densification. Therefore, the extremely difficult sintering and densification of boron carbide has limited its industrial application to a certain extent.
[0003] Existing studies have shown that the microstructure of ceramic materials has an important influence on their mechanical properties, including the uniformity of the second phase distribution, density, grain size and grain boundaries. During the reaction sintering process, coarse raw material particles can easily cause particle agglomeration inside the final ceramic. These agglomeration phenomena not only lead to uneven distribution of the second phase in the composite ceramic, but also significantly increase the fluctuation of the mechanical properties of the material. At present, during the sintering process of ceramic materials, external constant pressure is applied to achieve ceramic densification, but in the later stage of sintering, the constant pressure can no longer provide sufficient driving force for grain boundary diffusion, so that the pores in the ceramic are difficult to close, and the density of the ceramic material cannot be further improved.
[0004] Therefore, it is necessary to provide a method for preparing a B4C-based composite ceramic material with a uniformly distributed second phase to solve the deficiencies in the prior art. Summary of the invention
[0005] The object of the present invention is to provide a composite ceramic containing B4C and a preparation method thereof. In the present invention, a composite ceramic with uniform second phase distribution is prepared by pressure change cyclic sintering, and the composite ceramic has fine grains, uniform microstructure, high hardness and fracture toughness.
[0006] In a first aspect, the present invention provides a method for preparing a composite ceramic containing B4C, comprising the following steps: mixing B4C powder, boron powder, and transition metal carbide powder, ball milling, and drying to obtain a precursor material; placing the precursor material in a vacuum environment and sequentially performing pre-sintering, pressure change cyclic sintering, and pressure relief and cooling to obtain a composite ceramic containing B4C; during the pre-sintering process, the temperature is raised from room temperature to a first temperature, then to a second temperature, and the first pressure is maintained; the pressure change cyclic sintering step specifically includes: at the second temperature, the first pressure is increased to a second pressure, then the pressure is reduced to the first pressure, and the process is repeated; after multiple pressurization-decompression cycles, the second temperature is increased to a third temperature, and pressurized to the second pressure, and then the temperature is maintained and sintered.
[0007] In the present invention, B4C powder, boron powder, and transition metal carbide powder are used as raw materials, and multiple pressurization-decompression cycle sintering technology is used at a specific temperature to prepare a composite ceramic material containing B4C with uniform distribution of the second phase (diboride), low density, high hardness, high strength, strong toughness, and uniform distribution of mechanical properties. Specifically, diboride is used as the main toughening phase, and the constant pressure is adjusted to dynamic pressure. The agglomeration of ceramic powders is destroyed by continuous pressure changes, and a greater sintering driving force is provided for powder sintering, thereby accelerating the densification of the green body; the uniformity of the second phase distribution is significantly improved, and the occurrence of particle agglomeration during the reaction sintering process is effectively prevented.
[0008] It should be noted that pressure sintering can be carried out in existing conventional equipment, for example, it can be carried out in a hot press furnace or a spark plasma sintering device, and the hot press furnace or the spark plasma sintering device is equipped with a hydraulic control system, which can adjust the pressure of pressure sintering and the adjustment range is large. Therefore, the method of the present invention has the advantages of short cycle, good repeatability, simple steps, and easy implementation.
[0009] In some embodiments, during the preparation of the precursor material, the content of B4C powder is 15-85%, the content of boron powder is 7-45%, and the content of transition metal carbide powder is 7-50% by mass.
[0010] In some embodiments, during the preparation of the precursor material, the transition metal carbide powder includes one or more of ZrC, TiC, Cr3C2, Mo2C, TaC, NbC, WC, VC or HEC.
[0011] In some embodiments, during the preparation of the precursor material, the purity of B4C powder is 99.9%, and the particle size is 0.5~2μm; the purity of boron powder is 95%, and the particle size is 0.5~2μm; the purity of transition metal carbide powder is 99.9%, and the particle size is 0.1~3.5μm.
[0012] In the present invention, by selecting B4C powder, boron powder and transition metal carbide powder with high purity as raw materials, the generation of impurities can be avoided, thereby further improving the performance of the prepared composite ceramics; by controlling the particle sizes of B4C powder, boron powder and transition metal carbide powder within a specific range, the materials can be mixed evenly, which is convenient for full reaction during the sintering process, thereby significantly improving the performance of the prepared composite ceramics.
[0013] In some embodiments, during the preparation of the precursor material, the ball milling step specifically includes: adding an organic solvent and a ball milling medium to the mixed material, and controlling the ball-to-material mass ratio to (0.5~1.5):1, and ball milling for 6~12 hours; wherein the organic solvent includes anhydrous ethanol, and the ball milling medium includes ZrO2.
[0014] In the present invention, the materials are further evenly dispersed and mixed through ball milling, which facilitates the full reaction of the materials during the sintering process and further improves the performance of the prepared composite ceramics.
[0015] In some embodiments, during the preparation of the precursor material, the drying step specifically includes: rotary evaporating the suspension obtained after ball milling at a temperature of 50-70°C for 0.5-1.5 hours, and continuing to dry at a temperature of 60-80°C for 10-14 hours.
[0016] In some embodiments, during the pre-sintering process, the heating rate from room temperature to the first temperature is 140-160° C. / min, and the heating rate to the second temperature is 90-110° C. / min, and the first pressure is 10-30 MPa.
[0017] In some embodiments, the first temperature is 500-700°C, and the second temperature is 1200-1400°C.
[0018] In some embodiments, the second pressure is 55~65MPa, the time for pressurization and decompression is 1~3min, and the number of pressurization-decompression cycle treatments is 3~12 times; the heating rate from the second temperature to the third temperature is 90~110℃ / min, and the third temperature is 1900~2000℃; the heat preservation sintering step specifically includes: the heat preservation time is 3~10min.
[0019] In a second aspect, the present invention provides a composite ceramic comprising B4C, wherein the composite ceramic is prepared by any one of the above-mentioned preparation methods.
[0020] In some embodiments, the Vickers hardness (HV1) of the composite ceramic is 31-40 GPa, and the fracture toughness is 4.1-6.0 MPa·m 1 / 2 .
[0021] The beneficial effects of the present invention are as follows: Different from the prior art, the present invention uses B4C powder, boron powder and transition metal carbide powder as raw materials, and adopts multiple pressurization-decompression cycle sintering technology at a specific temperature to prepare a composite ceramic material containing B4C with uniform distribution of the second phase (diboride), low density, high hardness, high strength, strong toughness and uniform distribution of mechanical properties. In addition, the preparation method of the present invention is simple, short in cycle, good in repeatability and easy to implement, and therefore has good practical application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The surface morphology of the composite ceramic material prepared by pressure sintering in Example 1 of the present invention after 5 and 10 pressure change cycle sintering respectively; Figure 2 The Weibull modulus analysis diagram is obtained by measuring the hardness of the composite ceramics prepared in Example 1 of the present invention and Comparative Example 1 and then calculating; Figure 3 This is a surface morphology of a composite ceramic material without pressure change cyclic sintering in Comparative Example 1 of the present invention; Figure 4 This is a surface morphology of a composite ceramic material without pressure change cyclic sintering in Comparative Example 2 of the present invention; Figure 5 The surface morphology images obtained in Example 1 (5 sinterings and 10 sinterings), Example 3 (5 sinterings and 10 sinterings), Comparative Example 1 and Comparative Example 2 of the present invention are divided into nine equal parts, and the average volume fraction of the second phase (diboride) in each equal part is respectively counted; Figure 6 1 and 2 are XRD diagrams of the composite ceramic materials prepared in Examples 1 and 3 of the present invention. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] The experimental methods without specific conditions in the examples are usually carried out according to conventional conditions and conditions described in the manual, or according to conditions recommended by the manufacturer. The general equipment, materials, reagents, etc. used are all available from commercial channels unless otherwise specified.
[0025] In the present invention, the purity of the B4C powder used is 99.9%, and the particle size is 0.5-2 μm; the purity of the boron powder is 95%, and the particle size is 0.5-2 μm; the purity of the transition metal carbide powder (including one or more of ZrC, TiC, Cr3C2, Mo2C, TaC, NbC, WC, VC or HEC) is 99.9%, and the particle size is 0.1-3.5 μm.
[0026] Example 1 A method for preparing a composite ceramic containing B4C comprises the following steps: S1. Preparation of raw material mixed powder: Select B4C powder, boron powder, TiC powder and Cr3C2 powder as raw materials, and the phase composition is 80vol% B4C and 20vol% (Ti 0.9 Cr 0.1 ) B2 Mix 40g of the raw materials, namely 18.06g B4C powder, 11.88g boron powder, 9.59g TiC powder, and 1.07g Cr3C2 powder; S2, ball milling: placing the mixed powder obtained in step S1 in a polytetrafluoroethylene tank, adding an equal mass of ZrO2 as a grinding medium, using anhydrous ethanol as a solvent, and ball milling for 12 hours using a swing mixer to obtain a suspension; S3, drying: using a rotary evaporator, at a temperature of 60° C., the suspension obtained in step S2 was rotary evaporated for 0.5 h, and then placed in a blast oven for further drying for 12 h to obtain a precursor material; S4, sintering: placing the precursor material obtained in step S3 in a graphite mold and performing spark plasma sintering; specifically, under vacuum conditions, heating from room temperature to 600°C at a heating rate of 150°C / min, at which time, the pressure is controlled to be 10MPa, and then heating to 1300°C at a heating rate of 100°C / min; then starting pressure sintering: first, pressurizing the pressure to 60MPa within 1min, and then reducing the pressure to 10MPa within 1min, which is a pressurization-decompression cycle, after 5 and 10 cycles respectively, continue to heat to 1900°C at a heating rate of 100°C / min, and at the same time pressurize to 60MPa, and keep the temperature and pressure for 5min; after sintering, cool with the furnace, take out the mold, separate the sintered body from the mold, and obtain B4C-(Ti 0.9 Cr 0.1 )B2 composite ceramic material.
[0027] Example 2 A method for preparing a composite ceramic containing B4C comprises the following steps: S1, raw material mixed powder preparation: select B4C powder, boron powder, TiC powder as raw materials, according to the phase composition of 80vol% B4C and 20vol% TiB2, mix 40g of the raw materials, i.e. 17.75g B4C powder, 12.18g boron powder, 10.68g TiC powder; S2, ball milling: placing the mixed powder obtained in step S1 in a polytetrafluoroethylene tank, adding an equal mass of ZrO2 as a grinding medium, using anhydrous ethanol as a solvent, and ball milling for 12 hours using a swing mixer to obtain a suspension; S3, drying: using a rotary evaporator, at a temperature of 60° C., the suspension obtained in step S2 was rotary evaporated for 0.5 h, and then placed in a blast oven for further drying for 12 h to obtain a precursor material; S4, sintering: placing the precursor material obtained in step S3 in a graphite mold and performing spark plasma sintering; specifically, under vacuum conditions, heating from room temperature to 600°C at a heating rate of 150°C / min, at which time, controlling the pressure to be 20MPa, and then heating to 1300°C at a heating rate of 100°C / min; then starting pressure sintering: first increasing the pressure to 60MPa within 2min, and then reducing the pressure to 20MPa within 2min, this is a pressurization-decompression cycle, after 5 and 10 cycles respectively, continue to increase the temperature to 1900°C at a heating rate of 100°C / min, and at the same time increase the pressure to 60MPa, and keep the temperature and pressure for 5min; after sintering is completed, cool with the furnace, take out the mold and separate the sintered body from the mold to obtain a B4C-TiB2 composite ceramic material.
[0028] Example 3 A method for preparing a composite ceramic containing B4C comprises the following steps: S1. Preparation of raw material mixed powder: Select B4C powder, boron powder, TiC powder and Cr3C2 powder as raw materials, and the phase composition is 70vol% B4C and 30vol% (Ti 0.9 Cr 0.1 ) B2 Mix 40g of the raw materials, namely 9.23g B4C powder, 16.66g boron powder, 13.45g TiC powder, and 1.50g Cr3C2 powder; S2, ball milling: placing the mixed powder obtained in step S1 in a polytetrafluoroethylene tank, adding an equal mass of ZrO2 as a grinding medium, using anhydrous ethanol as a solvent, and ball milling for 12 hours using a swing mixer to obtain a suspension; S3, drying: using a rotary evaporator, at a temperature of 60° C., the suspension obtained in step S2 was rotary evaporated for 0.5 h, and then placed in a blast oven for further drying for 12 h to obtain a precursor material; S4, sintering: placing the precursor material obtained in step S3 in a graphite mold and performing spark plasma sintering; specifically, under vacuum conditions, heating from room temperature to 600°C at a heating rate of 150°C / min, at which time, the pressure is controlled to be 10MPa, and then heating to 1300°C at a heating rate of 100°C / min; then starting pressure sintering: first, pressurizing the pressure to 60MPa within 1min, and then reducing the pressure to 10MPa within 1min, which is a pressurization-decompression cycle, after 5 and 10 cycles respectively, continue to heat to 1900°C at a heating rate of 100°C / min, and at the same time pressurize to 60MPa, and keep the temperature and pressure for 5min; after sintering, cool with the furnace, take out the mold, separate the sintered body from the mold, and obtain B4C-(Ti 0.9 Cr 0.1 )B2 composite ceramic material.
[0029] Example 4 A method for preparing a composite ceramic containing B4C comprises the following steps: S1, raw material mixed powder preparation: select B4C powder, boron powder, ZrC powder as raw materials, according to the phase composition of 70vol% B4C and 30vol% ZrB2, mix 40g of the raw materials, i.e. 6.86g B4C powder, 13.46g boron powder, 20.35g ZrC powder; S2, ball milling: placing the mixed powder obtained in step S1 in a polytetrafluoroethylene tank, adding an equal mass of ZrO2 as a grinding medium, using anhydrous ethanol as a solvent, and ball milling for 12 hours using a swing mixer to obtain a suspension; S3, drying: using a rotary evaporator, at a temperature of 60° C., the suspension obtained in step S2 was rotary evaporated for 0.5 h, and then placed in a blast oven for further drying for 12 h to obtain a precursor material; S4, sintering: placing the precursor material obtained in step S3 in a graphite mold and performing spark plasma sintering; specifically, under vacuum conditions, heating from room temperature to 600°C at a heating rate of 150°C / min, at which time, controlling the pressure to 30MPa, and then heating to 1300°C at a heating rate of 100°C / min; then starting pressure sintering: first increasing the pressure to 60MPa within 1min, and then reducing the pressure to 30MPa within 2min, which is a pressurization-decompression cycle, after 5 and 10 cycles respectively, continue to increase the temperature to 1900°C at a heating rate of 100°C / min, and at the same time increase the pressure to 60MPa, and keep the temperature and pressure for 5min; after sintering is completed, cool with the furnace, take out the mold and separate the sintered body from the mold to obtain the B4C-ZrB2 composite ceramic material.
[0030] Example 5 A method for preparing a composite ceramic containing B4C comprises the following steps: S1. Preparation of raw material mixed powder: Select B4C powder, boron powder, TiC powder and VC powder as raw materials, and the phase composition is 70vol% B4C and 30vol% (TiC 0.7 V 0.3 ) B2 Mix 40g of the raw materials, namely 8.71g B4C powder, 17.00g boron powder, 10.44g TiC powder, 4.70g VC powder; S2, ball milling: placing the mixed powder obtained in step S1 in a polytetrafluoroethylene tank, adding an equal mass of ZrO2 as a grinding medium, using anhydrous ethanol as a solvent, and ball milling for 12 hours using a swing mixer to obtain a suspension; S3, drying: using a rotary evaporator, at a temperature of 60° C., the suspension obtained in step S2 was rotary evaporated for 0.5 h, and then placed in a blast oven for further drying for 12 h to obtain a precursor material; S4, sintering: placing the precursor material obtained in step S3 in a graphite mold and performing spark plasma sintering; specifically, under vacuum conditions, heating from room temperature to 600°C at a heating rate of 150°C / min, at which time, the pressure is controlled to be 10MPa, and then heating to 1300°C at a heating rate of 100°C / min; then starting pressure sintering: first, pressurizing the pressure to 60MPa within 2min, and then reducing the pressure to 10MPa within 2min, which is a pressurization-decompression cycle, after 5 and 10 cycles respectively, continue to heat to 1900°C at a heating rate of 100°C / min, and at the same time pressurize to 60MPa, and keep the temperature and pressure for 5min; after sintering, cool with the furnace, take out the mold, separate the sintered body from the mold, and obtain B4C-(Ti 0.7 V 0.3 )B2 composite ceramic material.
[0031] Example 6 A method for preparing a composite ceramic containing B4C comprises the following steps: S1. Preparation of raw material mixed powder: Select B4C powder, boron powder, ZrC powder and NbC powder as raw materials, and the phase composition is 80vol% B4C and 20vol% (Zr 0.8 Nb 0.2 ) B2 Mix 40g of the raw materials, namely 17.49g B4C powder, 9.12g boron powder, 11.03g ZrC powder, and 2.80g NbC powder; S2, ball milling: placing the mixed powder obtained in step S1 in a polytetrafluoroethylene tank, adding an equal mass of ZrO2 as a grinding medium, using anhydrous ethanol as a solvent, and ball milling for 12 hours using a swing mixer to obtain a suspension; S3, drying: using a rotary evaporator, at a temperature of 60° C., the suspension obtained in step S2 was rotary evaporated for 0.5 h, and then placed in a blast oven for further drying for 12 h to obtain a precursor material; S4, sintering: placing the precursor material obtained in step S3 in a graphite mold and performing spark plasma sintering; specifically, under vacuum conditions, heating from room temperature to 600°C at a heating rate of 150°C / min, at which time, the pressure is controlled to be 20MPa, and then heating to 1300°C at a heating rate of 100°C / min; then starting pressure sintering: first, increasing the pressure to 60MPa within 1min, and then reducing the pressure to 20MPa within 1min, which is a pressurization-decompression cycle, after 5 and 10 cycles respectively, continuing to increase the temperature to 1900°C at a heating rate of 100°C / min, and at the same time increasing the pressure to 60MPa, and keeping the temperature and pressure for 5min; after sintering, cooling with the furnace, taking out the mold, separating the sintered body from the mold, and obtaining B4C-(Zr 0.8 Nb 0.2 )B2 composite ceramic material.
[0032] Example 7 A method for preparing a composite ceramic containing B4C comprises the following steps: S1. Preparation of raw material mixed powder: Select B4C powder, boron powder, ZrC powder and NbC powder as raw materials, and mix them into a mixture of 90 vol% B4C and 10 vol% (Zr 0.8 Nb 0.2 ) B2 Mix 40g of the raw materials, namely 27.34g B4C powder, 5.13g boron powder, 6.21g ZrC powder, and 1.58g NbC powder; S2, ball milling: placing the mixed powder obtained in step S1 in a polytetrafluoroethylene tank, adding an equal mass of ZrO2 as a grinding medium, using anhydrous ethanol as a solvent, and ball milling for 12 hours using a swing mixer to obtain a suspension; S3, drying: using a rotary evaporator, at a temperature of 60° C., the suspension obtained in step S2 was rotary evaporated for 0.5 h, and then placed in a blast oven for further drying for 12 h to obtain a precursor material; S4, sintering: placing the precursor material obtained in step S3 in a graphite mold and performing spark plasma sintering; specifically, under vacuum conditions, heating from room temperature to 600°C at a heating rate of 150°C / min, at which time, the pressure is controlled to be 10MPa, and then heating to 1300°C at a heating rate of 100°C / min; then starting pressure sintering: first, pressurizing the pressure to 60MPa within 1min, and then reducing the pressure to 10MPa within 1min, which is a pressurization-decompression cycle, after 5 and 10 cycles respectively, continue to heat to 1900°C at a heating rate of 100°C / min, and at the same time, pressurize to 60MPa, and keep the temperature and pressure for 5min; after sintering, cool with the furnace, take out the mold, separate the sintered body from the mold, and obtain B4C-(Zr 0.8 Nb 0.2 )B2 composite ceramic material.
[0033] Comparative Example 1 The preparation method of the composite ceramic containing B4C in this comparative example is basically the same as that in Example 1, except that the sintering in step S4 is as follows: the precursor material obtained in step S3 is placed in a graphite mold and subjected to spark plasma sintering; specifically, under vacuum conditions, the temperature is raised from room temperature to 600°C at a heating rate of 150°C / min, at which time, the pressure is controlled to be 10MPa, and the temperature is continued to be raised to 1900°C at a heating rate of 100°C / min, and the pressure is increased to 60MPa at the same time, and the temperature is maintained for 5min; after the sintering is completed, the furnace is cooled, and the sintered body is separated from the mold after the mold is taken out, so as to obtain B4C-(Ti 0.9 Cr 0.1 )B2 composite ceramic material.
[0034] Comparative Example 2 The preparation method of the composite ceramic containing B4C in this comparative example is basically the same as that in Example 3, except that the sintering in step S4 is as follows: the precursor material obtained in step S3 is placed in a graphite mold and subjected to spark plasma sintering; specifically, under vacuum conditions, the temperature is raised from room temperature to 600°C at a heating rate of 150°C / min, at which time, the pressure is controlled to be 10MPa, and the temperature is continued to be raised to 1900°C at a heating rate of 100°C / min, and the pressure is increased to 60MPa at the same time, and the temperature is maintained for 5min; after the sintering is completed, the furnace is cooled, and the mold is taken out and the sintered body is separated from the mold to obtain B4C-(Ti 0.9 Cr 0.1 )B2 composite ceramic material.
[0035] Performance Testing The Vickers hardness and fracture toughness of the composite ceramic materials prepared in Examples 1-7 and Comparative Examples 1-2 were tested, and the results are shown in Table 1 below.
[0036] Table 1 Vickers hardness and fracture toughness results of composite ceramic materials
[0037] From the data in Table 1, it can be seen that the composite ceramic materials prepared after 5 and 10 pressure change cycle sintering in Examples 1-7 have good Vickers hardness and fracture toughness, and the performance of the composite ceramic materials is related to the number of pressure change cycle sintering. As the number of pressure change cycle sintering increases, the Vickers hardness and fracture toughness of the composite ceramic materials decrease to a certain extent, but are at a good level. In Comparative Examples 1 and 2, no pressure change cycle sintering was used. It was found that the Vickers hardness of the prepared composite ceramic materials decreased significantly. The results show that in the present invention, by using pressure change cycle sintering, the performance of the composite ceramic materials can be significantly improved.
[0038] The surface morphology of the composite ceramic material prepared by pressure sintering in Example 1 after 5 and 10 pressure change cycles were tested. The results are as follows: Figure 1 shown.
[0039] from Figure 1 It can be seen that the second phase of the composite ceramic material after 5 and 10 cycles of sintering is more uniformly distributed, but the agglomerate size after 5 cycles of sintering is smaller than that after 10 cycles of sintering. The results show that multiple cycles of sintering can make the second phase of the composite ceramic material uniformly distributed.
[0040] The hardness of the composite ceramics prepared in Example 1 and Comparative Example 1 was measured, and the Weibull modulus analysis diagram of the composite ceramics was calculated. Figure 2 shown.
[0041] from Figure 2 It can be seen that the Weibull modulus of the composite ceramic materials obtained after 5 and 10 pressure change cycle sintering are 60.40 and 20.44, respectively, which are 310% and 38.76% higher than those without pressure change cycle sintering. The results show that the second phase distribution of the material after 5 pressure change cycle sintering is more uniform and the mechanical properties are better. After 10 cycles, the uniformity decreases but the performance is still better than that of the material without pressure change cycle sintering.
[0042] The surface morphology of the composite ceramic materials prepared in Comparative Example 1 and Comparative Example 2 was tested, and the results were as follows: Figure 3 and 4 shown.
[0043] from Figure 3 and 4It can be seen that the second phase in the composite ceramic material without pressure change cyclic sintering is unevenly distributed and has large agglomeration.
[0044] The surface morphology images obtained in Example 1 (5 sinterings and 10 sinterings), Example 3 (5 sinterings and 10 sinterings), Comparative Example 1 and Comparative Example 2 were divided into nine equal parts, and the average volume fraction of the second phase (diboride) in each equal part was calculated. The results are as follows: Figure 5 shown.
[0045] from Figure 5 It can be seen that the average volume fraction of each group is basically consistent with the volume fraction of the second phase of each ceramic material; and from the size of the error bar, it can also be seen that the uniformity of the second phase distribution is improved the most after the ceramic materials of each component are sintered 5 times with pressure change cycles.
[0046] The composite ceramic materials prepared in Example 1 and Example 3 were subjected to XRD testing, and the results are as follows: Figure 6 shown.
[0047] from Figure 6 It can be seen that the prepared composite ceramic material has only two phases: B4C phase and diboride phase.
[0048] In summary, the present invention adopts multiple pressurization-decompression cycle sintering technology to prepare a composite ceramic material containing B4C with uniform second phase distribution, low density, high hardness, high strength, strong toughness, and uniform distribution of mechanical properties.
[0049] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.
[0050] The above-mentioned embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a composite ceramic containing B4C, characterized in that: The steps include: The precursor material is obtained by mixing B4C powder, boron powder and transition metal carbide powder, ball milling and drying. Placing the precursor material in a vacuum environment and sequentially performing pre-sintering, pressure-changing cyclic sintering, and pressure-releasing and cooling to obtain a composite ceramic containing B4C; During the pre-sintering process, the temperature is raised from room temperature to a first temperature, and then to a second temperature, while maintaining a first pressure; The pressure change cyclic sintering step specifically includes: at a second temperature, increasing the first pressure to a second pressure, then reducing the pressure to the first pressure, and repeating the process; After multiple cycles of pressurization and decompression, the second temperature is raised to the third temperature, and the pressure is increased to the second pressure, followed by sintering at the same time.
2. The preparation method according to claim 1, characterized in that: In the preparation process of the precursor material, the content of the B4C powder is 15-85% by mass, the content of the boron powder is 7-45% by mass, and the content of the transition metal carbide powder is 7-50% by mass.
3. The preparation method according to claim 1, characterized in that: In the preparation process of the precursor material, the transition metal carbide powder includes one or more of ZrC, TiC, Cr3C2, Mo2C, TaC, NbC, WC, VC or HEC.
4. The preparation method according to claim 1, characterized in that: In the preparation process of the precursor material, the purity of the B4C powder is 99.9%, and the particle size is 0.5-2 μm; the purity of the boron powder is 95%, and the particle size is 0.5-2 μm; The transition metal carbide powder has a purity of 99.9% and a particle size of 0.1-3.5 μm.
5. The preparation method according to claim 1, characterized in that: In the preparation process of the precursor material, the ball milling step specifically includes: adding an organic solvent and a ball milling medium to the mixed material, and controlling the ball-to-material mass ratio to be (0.5-1.5):1, and ball milling for 6-12 hours; Wherein, the organic solvent includes anhydrous ethanol, and the ball milling medium includes ZrO2.
6. The preparation method according to claim 1, characterized in that: In the preparation process of the precursor material, the drying step specifically includes: rotary evaporating the suspension obtained after ball milling at a temperature of 50-70°C for 0.5-1.5h, and continuing to dry at a temperature of 60-80°C for 10-14h.
7. The preparation method according to claim 1, characterized in that: During the pre-sintering process, the heating rate from room temperature to the first temperature is 140-160° C. / min, and the heating rate to the second temperature is 90-110° C. / min. The first pressure is 10-30 MPa.
8. The preparation method according to claim 7, characterized in that: The first temperature is 500-700°C, and the second temperature is 1200-1400°C.
9. The preparation method according to claim 8, characterized in that: The second pressure is 55-65 MPa, the pressurization and decompression times are both 1-3 min, and the number of pressurization-decompression cycle treatments is 3-12 times; The heating rate of heating the second temperature to the third temperature is 90-110° C. / min, and the third temperature is 1900-2000° C.; The heat preservation and sintering step specifically includes: the heat preservation time is 3 to 10 minutes.
10. A composite ceramic comprising B4C, characterized in that: The composite ceramic is prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of boron carbide ceramic
CN113387705A
Sintering method of completely-densified high-proportion covalent bond ceramic
CN114368971A
B4C-TiB2 conductive composite ceramic and preparation method thereof
CN114685168A
